2013
DOI: 10.1111/cas.12103
|View full text |Cite
|
Sign up to set email alerts
|

Combination of guanine arabinoside and Bcl‐2 inhibitor YC137 overcomes the cytarabine resistance in HL‐60 leukemia cell line

Abstract: Cytarabine (ara‐C) is the key agent for treating acute myeloid leukemia. After being transported into leukemic cells, ara‐C is phosphorylated, by several enzymes including deoxycytidine kinase (dCK), to ara‐C triphosphate (ara‐CTP), an active metabolite, and then incorporated into DNA, thereby inhibiting DNA synthesis. Therefore, the cytotoxicity of ara‐C depends on the production of ara‐CTP and the induction of apoptosis. Here, we established a new ara‐C‐resistant acute myeloid leukemia cell line (HL‐60/ara‐C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Our previous study demonstrated that the Bcl-2 inhibitor YC137 is cytotoxic to ara-C-resistant leukemic cells [16]. ABT737, which inhibits Bcl-2 and Bcl-xL, effectively induced death in CAFdA-resistant leukemic cells [17].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our previous study demonstrated that the Bcl-2 inhibitor YC137 is cytotoxic to ara-C-resistant leukemic cells [16]. ABT737, which inhibits Bcl-2 and Bcl-xL, effectively induced death in CAFdA-resistant leukemic cells [17].…”
Section: Discussionmentioning
confidence: 97%
“…Kinases (dCK, dGK), transporters (hENT1, hENT2, hENT3, hCNT3), and apoptosis-related factors (Bcl-2, Mcl-1, Bad, Bim, Bax, Bak) were determined using Western blot analysis [16]. Mouse monoclonal anti-dCK (Abcam Cambridge, UK), rabbit polyclonal anti-dGK (Abcam), mouse monoclonal anti-hENT1 (Santa Cruz Biotechnology, Dallas, TX, USA), rabbit monoclonal anti-hENT2 (Abcam), rabbit polyclonal anti-hCNT3 (Abcam), rabbit polyclonal anti-Bcl-2 (Cell Signaling Technology, Beverly, MA, USA), rabbit polyclonal anti-Mcl-1 (Cell Signaling Technology), rabbit monoclonal anti-Bad (Cell Signaling Technology), anti-Bim (Cell Signaling Technology), anti-Bax (Cell Signaling Technology), anti-Bak (Cell Signaling Technology), and anti-actin (Sigma-Aldrich, St. Louis, MO, USA) antibodies were used as the primary antibodies.…”
Section: Determination Of Kinases Nucleoside Transporters and Apoptmentioning
confidence: 99%
See 1 more Smart Citation
“…Dihalogenated nucleosides 3a-d were tested for their ability to inhibit the growth of HL-60 cells in culture. Monohalogenated cladribine, which is known to efficiently inhibit HL-60 cells [18,19], was used as positive control. While for cladribine an IC50 value of 0.22 µ M [± 0.11 µ M] was determined, 50% of inhibition by the dihalogenated nucleoside analogues was observed for concentrations between 10 and 100 µ M (Figure 2).…”
Section: Effect Of Dihalogenated Nucleoside Analogues On Cell Growthmentioning
confidence: 99%
“…Chemical shifts are reported in parts per million (ppm) and are referenced to the residual solvent resonance as the internal standard ( 1 H NMR: δ = 2.50 ppm for DMSO-d 5 ; 13 C NMR: δ = 39.52 ppm for DMSO-d 6 ) [37]. 19 F NMR spectra are referenced in compliance with the unified scale for NMR chemical shifts as recommended by the IUPAC stating the chemical shift relative to CCl 3 F [38] . Data are reported as follows: chemical shift, multiplicity (s = singlet, d = doublet, m c = centrosymmetric multiplet, br = broad signal), coupling constants (Hz), and integration.…”
Section: Nmr Analysismentioning
confidence: 99%